2017
DOI: 10.3389/fphys.2017.01004
|View full text |Cite
|
Sign up to set email alerts
|

P311 Deficiency Leads to Attenuated Angiogenesis in Cutaneous Wound Healing

Abstract: P311 was identified to markedly promote cutaneous wound healing by our group. Angiogenesis plays a key role in wound healing. In this study, we sought to define the role of P311 in skin wound angiogenesis. It was noted that P311 was expressed in endothelial cells in the dermis of murine and human skin wounds. The expression of P311 was confirmed in cultured murine dermal microvascular endothelial cells (mDMECs). Moreover, it was found that knockout of P311 could attenuate the formation of tubes and motility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…While in myofibroblasts, it enhanced the activity of Ral A (Shi et al, 2006). Other known functions of P311 like the regulation of blood pressure homeostasis (Badri et al, 2013), the regulation of development of fibrosis (Yao et al, 2015; Cheng et al, 2017), the regulation of wounds (Yao et al, 2017), angiogenesis (Wang et al, 2017) and so on are shown in Supplementary Material 8. P311–TGF-β axis signaling was demonstrated to be important signaling that is related to the processes above.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While in myofibroblasts, it enhanced the activity of Ral A (Shi et al, 2006). Other known functions of P311 like the regulation of blood pressure homeostasis (Badri et al, 2013), the regulation of development of fibrosis (Yao et al, 2015; Cheng et al, 2017), the regulation of wounds (Yao et al, 2017), angiogenesis (Wang et al, 2017) and so on are shown in Supplementary Material 8. P311–TGF-β axis signaling was demonstrated to be important signaling that is related to the processes above.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the P311 WT mice, the number of inflammatory cells was much lower in P311 KO mice, while the mRNA level of CD14 and CD16 was also much lower in P311 KO mice (Figure 3). It has been proven that P311 could regulate wound healing by accelerating reepithelization (Yao et al, 2017) or by affecting angiogenesis (Wang et al, 2017). It therefore implies that P311 might also regulate wound healing by affecting the inflammation response during wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies were conducted in United States of America (25.9%) [ 27 , 35 40 ]; Japan (18.5%) [ 26 , 41 44 ]; Germany (11.1%) [ 45 47 ]; Brazil, Canada, and China (7.4%, each) [ 28 , 29 , 48 51 ]; and Australia, Singapore, Netherlands, Spain, Taiwan, and Switzerland (3.7%, each) [ 52 57 ]. The approval for the use of animals in experimental procedures by the Animal Use and Care Committee was mentioned in 85.2% of the studies, and the statistical analyses performed were specified in 81.5% of the studies.…”
Section: Resultsmentioning
confidence: 99%